Competition and cooperation in economics and business (2018)
This book is one of the five volumes of proceedings that provides an opportunity for readers to engage with selected papers presented at the 1st Asia-Pacific Forum for Research in Social Sciences and Humanities (1st APRISH) conference held in Depok (Indonesia) on November 7–9, 2016. Quoting the theme of the conference “Competition and Cooperation in the Globalized World,” this book would be a valuable contribution to get a better understanding of the future global challenges. Readers will find a broad range of research reports on topics ranging from globalization, poverty, population and some macroprudential perspectives on managing the risk of a more integrated world. One of the unique and valuable dimensions of this conference is the capability for blending the chemistries among educators, students, and researchers from around the world to discuss globalization in a broad spectrum. The reader will discover both common challenges and creative solutions emerge from very diverse settings. The relevance of the conference’s theme, towards an evidence-based society, for a variety of disciplines, is reflected in the diverse range of papers that have been submitted for publication. These serve to demonstrate the natural attraction of the conference for sharing ideas and findings within an international community. Overall, the conference was undoubtedly very successful. Plenary lectures and presentations were successfully bridging the gap between the different fields of social sciences, making it possible for non-experts in a given area to gain insight into new areas. Also, among the speakers there were some young scientists, namely, doctoral, master’s and undergraduate students, who bring new perspectives to their fields. The editors would like to thank all those who have contributed to submit full papers for this conference. We received 101 papers from the conference and after a rigorous review, only 49 papers were accepted to be published in this volume. We would like to express our appreciation and gratitude to the scientific committee and the reviewers who have selected and reviewed the papers, and also to the technical editor’s team who helped carry out the page layout and check the consistency of the papers with the publisher’s template. It is an honor to publish selected papers in this volume by CRC Press/Balkema (Taylor & Francis Group). Finally, we would like to thank the steering committee, the chairman of the conference, the members of organizing committee involved in preparing and organizing the conference, and the financial support from Universitas Indonesia.